Assessment of postural stabilization in three task oriented movements in people with multiple sclerosis. (December 2014) - Cattaneo, Davide; Rabuffetti, Marco; Bovi, Gabriele; Mevio, Elisabetta; Jonsdottir, Johanna; Ferrarin, Maurizio
Abstract Purpose: In accordance with the Task Oriented Approach, clinicians need assessment procedures providing information on the execution of multiple tasks. Instrumented task assessment can add information regarding sensory–motor strategies, difficult to assess purely by clinical observation. It has been shown that People with Multiple Sclerosis (PwMS) have difficulties in maintaining upright balance, but little is known about their ability to achieve a stable posture after the execution of tasks related to activities of daily living. The aim of the present study was to assess postural stabilization in a population of PwMS. Methods: Twenty Healthy Subjects (HS) and twenty PwMS were assessed in three tasks leading to a quiet erect posture: sit-to-stand, taking a step forward, bending forward. Antero-posterior ground reaction force was measured by a force platform and interpolated by a model providing information on the initial instability after task execution (Transitional_Sway), the time required to dissipate this initial instability (Stabilization_Time), and their stability in quiet upright posture (Static_Sway). Results: PwMS had statistically significant altered performance in comparison to HS: their instability after task execution (Transitional_Sway) was higher in bending and sit-to-stand (p < 0.05), their stabilization time (Stabilization_Time) was longer in bending and step forward (p < 0.05). Static_Sway was higher in all tasks (p < 0.05) indicating imbalance also in quiet upright posture. Implications for Rehabilitation PwMS experience balance disorders in the transition between movement and the upright posture. Transitional disorders are related to difficulties in the execution of the movement itself, or to difficulties in reducing body sway after the movement. Tailored rehabilitation program can be implement to reduce impairments during the movement itself promoting coordination between body segments during the movement, muscle strength, joint mobility, or in the following postural stabilization phase improving subject's perception of the position and movement of the centre of mass in upright position.